2021
DOI: 10.1038/s41598-021-94481-1
|View full text |Cite
|
Sign up to set email alerts
|

The change of gut microbiota in MDD patients under SSRIs treatment

Abstract: The alterations in the gut microbiota have been reported to be correlated with the development of depression. The purpose of this study was to investigate the changes of intestinal microbiota in depressed patients after antidepressant treatment. We recruited 30 MDD patients (MDD group) and 30 healthy controls (control group). The MDD group received individualized treatment with escitalopram at a maximum dose of 20 mg/day. After depressive symptoms improved to a HAMD scale score > 50%, a fecal sample was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…Four studies included subgroups of the data. Subgroups included participants either aged 18–29 years or 30–59 years [ 69 ], males or females [ 70 ], active MDD cases or those considered in remission (R-MDD) [ 73 ] and MDD patients at baseline then after antidepressant treatment [ 89 ]. Results for these subgroups were extracted separately and compared to their control group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies included subgroups of the data. Subgroups included participants either aged 18–29 years or 30–59 years [ 69 ], males or females [ 70 ], active MDD cases or those considered in remission (R-MDD) [ 73 ] and MDD patients at baseline then after antidepressant treatment [ 89 ]. Results for these subgroups were extracted separately and compared to their control group.…”
Section: Resultsmentioning
confidence: 99%
“…Another study observed correlations between specific bacterial taxa and functional pathways within the KEGG orthologue database; however, they did not report what the specific pathways were, only providing the KEGG identification number [ 88 ]. Of the studies that examined multiple pathways and reported differences ( N = 9), MDD was associated with an enrichment of: glycan biosynthesis and metabolism (33%; N = 3/9 reported studies) [ 86 , 89 ]; lipopolysaccharide biosynthesis and biosynthesis proteins (33%; N = 3/9 reported studies) [ 72 , 85 ]; and transport and catabolism pathways (33%; N = 3/9 reported studies) [ 86 , 89 ], compared to controls. Conversely, cell motility and secretion (33%; N = 3/9 reported studies) [ 71 , 89 ] and membrane transport (33%; N = 3/9 reported studies) [ 86 , 89 ] were pathways enriched in controls compared to cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations